2021
DOI: 10.1371/journal.pone.0254239
|View full text |Cite
|
Sign up to set email alerts
|

An improved Wolf pack algorithm for optimization problems: Design and evaluation

Abstract: Wolf Pack Algorithm (WPA) is a swarm intelligence algorithm that simulates the food searching process of wolves. It is widely used in various engineering optimization problems due to its global convergence and computational robustness. However, the algorithm has some weaknesses such as low convergence speed and easily falling into local optimum. To tackle the problems, we introduce an improved approach called OGL-WPA in this work, based on the employments of Opposition-based learning and Genetic algorithm with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…This may involve combining regularization techniques with swarm intelligence optimization algorithms and ensemble methods to develop more reliable and generalizable models for genomic analysis. For example, the initial parameters of the model can be further optimized through the swarm intelligence optimization algorithm, such as the whale optimization algorithm (Brodzicki et al, 2021), Harris Hawks optimization algorithm (Qu et al, 2021), and wolf pack Frontiers in Genetics frontiersin.org optimization algorithm (Chen et al, 2021), to obtain more accurate results. Additionally, efforts to improve data quality and increase sample sizes can help reduce the risk of overfitting and enhance the robustness of artificial neural network-based predictive models in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…This may involve combining regularization techniques with swarm intelligence optimization algorithms and ensemble methods to develop more reliable and generalizable models for genomic analysis. For example, the initial parameters of the model can be further optimized through the swarm intelligence optimization algorithm, such as the whale optimization algorithm (Brodzicki et al, 2021), Harris Hawks optimization algorithm (Qu et al, 2021), and wolf pack Frontiers in Genetics frontiersin.org optimization algorithm (Chen et al, 2021), to obtain more accurate results. Additionally, efforts to improve data quality and increase sample sizes can help reduce the risk of overfitting and enhance the robustness of artificial neural network-based predictive models in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the local carbon emissions trading policy (CETP) also has an impact on it. Chen [12] analyzed panel data for 282 prefecture-level and above cities in China from 2007 to 2017, and found that CETP can significantly improve the efficiency of carbon emissions in pilot cities.…”
Section: Related Workmentioning
confidence: 99%
“…The act of rounding up is the last step of the wolf pack's hunting behavior, in which the wolves summoned by the head wolf attack the prey. When the hunting is completed, the prey obtained will be distributed to the wolf that has contributed the most to the hunting action in priority, in order of the degree of contribution in the hunting, and finally to the wolf with the least merit [20].…”
Section: The Basic Principle Of the Wolf Pack Optimization Algorithmmentioning
confidence: 99%